DEVELOPMENT OF HUMAN CAPITAL AND SOCIAL CAPITAL AFFECTING THE LOCAL DEVELOPMENT OF SUBDISTRICT MUNICIPALITIES IN PHETCHABUN PROVINCE - Yomin, Jariya (Journal of MCU Nakhondhat, 2024)
The research purposes were 1) To study the local development levels of subdistrict municipalities in Phetchabun Province; 2) To analyze the development of human capital and social capital affecting the local development of subdistrict municipalities in Phetchabun Province; and 3) To propose the guidelines for developing the local development of subdistrict municipalities in Phetchabun Province. This was the qualitative and quantitative research. The population was the people aged 18 years and over who had voting right in the area of subdistrict municipalities of Phetchabun Province; the sample group of quantitative research was the 400 people, the research instrument was the questionnaire; the sample group of qualitative research was the 20 people, the research instrument was the in-depth interview form. The statistics used to analyze the data are descriptive statistics, including frequency, percentage, mean, and standard deviation. and inferential statistics Multiple regression analysis With ready-made computer programs, research results found that 1) Local development in Phetchabun province Overall, it is at a high level. The highest mean value was in the area of ​​infrastructure (𝑥̅ = 3.62, S.D. = 0.45) and the least mean value was in the area of ​​economy, agriculture, goods and products, and tourism (𝑥̅ = 3.37, S.D. = 0.44); 2) The development of human capital and social capital in the areas of natural resource capital, human capital, increasing management efficiency, institutional capital, reducing health risk factors, promoting participation in national development, and knowledge development affected the local development of subdistrict municipalities in Phetchabun Province with a statistical significance level .05; and 3) This research findings had recommendations for concrete human capital development to be the important force in local development, including promoting tourism which is the good economic drivers in Phetchabun Province.